The Efforts of Bhabinkamtibmas through the Door to Door System in Preventing The Criminal Action of The Weighting by Weighting in the Jurisdiction of The Klaten Police - Kristianto Dwi Anggoro Kris (Advances in Police Science Research Journal, 2022)
This research is motivated by the increase in Theft By Weight cases that occurred in the jurisdiction of the Klaten Resort Police in 2018 to 2020 due to the effects of the Covid-19 pandemic and the impact on decreasing economic growth. Another effect of this pandemic is the occurrence of layoffs which resulted in an increase in the unemployment rate in Klaten. This unemployment rate causes crime rates to increase because people want to meet their basic needs instantly in the midst of a pandemic situation. Therefore, it is necessary to take preventive measures in reducing the number of drains in Klaten Regency. The step taken is to implement a system called Door To Door System by the Bhabinkamtibmas Unit. In this case the researcher is interested in researching the Door To Door System and examining its implementation and the factors that influence it. The analysis knife of this research uses Communication Theory, Management Theory, and Prevention Theory. While the concepts used are Bhabinkamtibmas, prevention, Door To Door, and criminal acts of Theft By Weight. This research was conducted with a qualitative approach and used a field research method. For analysis and data collection is by means of interviews, observations, document study data. The results of the study found that the implementation of the Door To Door System was not optimal in preventing the crime of stealing in Klaten Regency. The research findings show that the number of Bhabinkamtibmas personnel is not commensurate with the number of villages, members of Bhabinkamtibmas have not prepared material on Curat, the implementation of AAP is still minimal, the results of carrying out tasks using the Door To Door System method do not yet exist, there are members of Bhabinkamtibmas who have not had Binmas qualification education and the lack of wasdal from the leadership. Based on the findings above, the authors provide solutions, namely directing members of Bhabinkamtibmas to be dikjur Bhabinkamtibmas, arranging the distribution of members of Bhabinkamtibmas based on ability and level of vulnerability, checking the readiness of members of Bhabinkamtibmas when AAP includes self-readiness, sarpras, material to be delivered, checking the implementation directly to the field, and giving rewards and punishments.